Взаємозв’язок готовності до ризику та відповідальності як професійно важливих якостей особистості охоронників у приватних охоронних організаціях - Чепіга, Л. П.; Chepiga, L. P.; ORCID: http://orcid.org/0000-0002-2519-5698 (Право і безпека. - 2015. - № 3 (58). - С. 160–165., 2015)
Встановлено, що охоронники приватних охоронних організацій (далі – ПОО) характеризуються тим же рівнем прагнення до ризику, що і люди, чия професійна діяльність не пов’язана з екстремальними ситуаціями. Однак структура взаємозв’язків готовності до ризику та відповідальності у охоронників та співробітників ПОО, які не пов’язані з охоронною діяльністю, суттєво відрізняється та свідчить, що готовність до ризику охоронників ПОО обумовлена глибоким та цілісним уявленням про відповідальність, розумінням її суті. Результати дослідження можуть бути використані при проведенні професійного відбору та психокорекційної роботи в приватних охоронних організаціях.

It is indicated that some scholars refer liability and willingness to take risks to professionally important qualities of guards – employees of private security companies. Thus, if liability is considered as absolutely positive professionally needed personal characteristics, then it is not so clear with readiness (predisposition) to take risks. Contradictory data on the impact of the predisposition to take risks on the effectiveness of professional activity is provided in the literature. Predisposition to take risks is often considered as a contraindication for private security activity, but it is also noted that the choice to take risks can be conscious, value conditioned decision, which guarantees effective performance of professional duties. During the conducted research the author has found out that the guards of private security organizations (hereinafter – PSO) are characterized by the same level of desire for risk as people whose professional activity is not related to extreme situations. However, the structure of relationships between the willingness to take risks and liability of guards and employees of PSO, who are not related to security activity, is significantly different. Such components of the willingness to take risks, as the desire for thrills and the search for new experiences of the guards of SPO are caused by profound and holistic understanding about liability, understanding of its essence, commitment and integrity, manifested in carrying out duties aimed at the social environment, as well as experience of positive emotions while performing responsible tasks. Besides, the liability associated with a sense of duty, reduces non-adaptive commitment for difficulties. Another situation is observed talking about SPO employees not related to security activity. Facial understanding of liability, focus on personal well-being and existence of negative emotions while performing responsible tasks lead to the fact that SPO employees, who do not exercise security activity, have no willingness to take risks.

Показано, что охранники частных охранных предприятий (далее – ЧОП) характеризуются тем же уровнем стремления к риску, что и люди, чья профессиональная деятельность не связана с экстремальными ситуациями. Однако структура взаимосвязей готовности к риску и ответственности у охранников и сотрудников ЧОП, не осуществляющих охранной деятельности, существенно отличается и свидетельствует о том, что готовность к риску охранников ЧОП обусловлена глубоким и целостным представлением об ответственности, пониманием её сути. Результаты исследования могут быть использованы при проведении профессионального отбора и психокоррекционной работы на частных охранных предприятиях.
Chepiga, L.P. (2015), “Relationship between the willingness to take risks and liability as professionally important qualities of guards in private security organizations” [“Vzaiemozviazok hotovnosti do ryzyku ta vidpovidalnosti yak profesiino vazhlyvykh yakostei osobystosti okhoronnykiv u pryvatnykh okhoronnykh orhanizatsiiakh”], Pravo i Bezpeka, No. 3, pp. 160–165.
Чепіга, Л. П. Взаємозв’язок готовності до ризику та відповідальності як професійно важливих якостей особистості охоронників у приватних охоронних організаціях // Право і безпека. - 2015. - № 3 (58). - С. 160–165.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; професійно важливі риси особистості; охоронна діяльність; готовність до ризику; відповідальність; приватна охоронна організація; professionally important qualities of the person; security activities; willingness to take risks; liability; private security organization; профессионально важные качества личности; охранная деятельность; готовность к риску; ответственность; частное охранное предприятие